Effectiveness of Different Neuromuscular Recovery Strategies in Elite Youth Female Football Players - Silvia Sedano; Sergio Maroto-Izquierdo (Sports)
This study aimed to assess the effectiveness of various active recovery strategies in youth female soccer players during competitive tournaments with limited recovery periods (i.e., 24–48 h). Twenty-two elite under-17 female football players participated in this randomized controlled trial, which encompassed fourteen 90 min official matches. Participants were randomly allocated to one of three recovery protocols: passive stretching, foam rolling, or lumbopelvic mobility exercises, which were implemented ten minutes after each match. Countermovement jump with free arm (CMJA) height was measured pre-intervention, immediately post-intervention, and 5 h post-intervention. Wellness perception was evaluated 24 h later. Significant enhancements in CMJA height were observed immediately after all recovery protocols and at 5 h post-intervention compared with pre-intervention (p < 0.001). The lumbopelvic mobility protocol yielded the most substantial improvement, significantly surpassing both stretching and foam rolling. Moreover, significant increases in wellness perception were observed following the foam rolling (p < 0.001, ES = 0.95) and mobility (p < 0.05, ES = 0.88) protocols, with the mobility protocol demonstrating a marginally larger effect size than stretching. Active recovery strategies significantly enhanced neuromuscular function and wellness perception in under-17 female soccer players. Lumbopelvic mobility exercises exhibited superior efficacy, suggesting that they should be prioritized in post-match recovery regimens.